Differential Flatness-Based Approach for Sensors and Actuators Fault Diagnosis of a Multirotor UAV. Issue 16 (2019) - Saied, M; Mahairy, T.; Francis, C.; Shraim, H.; Mazeh, H.; Rafei, M. El
Abstract: This paper deals with sensors and actuators fault detection in multirotor unmanned aerial vehicles whose dynamics are modeled as nonlinear systems. The considered approach is based on the differential flatness property of flat systems that provide analytical redundancy where every control input and system state can be expressed as a function of the flat outputs. By comparing the real measurements with their corresponding estimations deduced from the differentially flat equations, residual signals are computed and used for fault diagnosis. For multirotor UAV systems, only one set of flat outputs can be found. In this paper, it is shown that this unique set can be used to detect and isolate both sensors and actuators faults and failures. The effectiveness of this approach is illustrated by numerical simulations on Matlab/Simulink, and also a real experimental application on a hexarotor UAV.